Trust in News in New Zealand 2020 - Myllylahti, Merja; Treadwell, Greg (AUT research centre for Journalism, Media and Democracy (JMAD), 2020)
This is the first JMAD report from the centre’s ongoing research project into the level of trust New Zealanders have in the news. It is produced in collaboration with the Reuters Institute for the Study of Journalism. With permission from the institute’s researchers, we have used the same survey questions and comparable sampling method they use in their annual Digital News Report (http://www.digitalnewsreport.org/). This allows international comparisons between levels of trust in the news in Aotearoa New Zealand and those 38 other countries covered by the Reuters project. While our survey was conducted during the coronavirus pandemic, and as New Zealanders were preparing for a national Covid-19 lockdown in late March 2020, it is impossible to know how coronavirus coverage and the lockdown may have affected trust in news. The survey data for our report was collected by New Zealand online market research company Horizon Research Ltd. The production of this report was funded by the Auckland University of Technology (AUT), and it has ethics approval from the AUT’s Ethics Committee (AUTEC).